Memórias de formação de um futuro professor: experiências na graduação que foram edificantes na minha formação inicial - ALBUQUERQUE, Charles Luã Araujo de (2020)
This article has monography format, which present the training experiences that experienced over the four-year undergraduate in the Bachelor's Degree in Integrated Education in Science, Mathematics and Languages of the Federal University of Pará. This article depicts the initial training teachers place on a course that brings a new methodological approach in teacher education for the early grades of elementary school of basic education, internalizing it to the exercise of effective teaching practices. Throughout this time I was in contact with job offers differentiated later to be applied in the classroom. This paper we look for and register the most significant moments in my teacher training, and how they made me reflect my own practice while graduating and as a future teacher. Through my experiences I seek to show that impact the teaching developed in the course had to build my teaching profile, and in my personal training. We can not put aside our emotional side and the story that we bring our academic journey. In other words, I bring this work interlace reflections of being professional and being personal that were woven during my graduation.